Value Incomparability and Indeterminacy - Constantinescu, Cristian (Ethical theory and moral practice, 2012)
Two competing accounts of value incomparability have been put forward in the recent literature. According to the standard account, developed most famously by Joseph Raz, ‘incomparability’ means determinate failure of the three classic value relations (better than, worse than, and equally good): two value-bearers are incomparable with respect to a value V if and only if (i) it is false that x is better than y with respect to V, (ii) it is false that x is worse than y with respect to V and (iii) it is false that x and y are equally good with respect to V. Most philosophers have followed Raz in adopting this account of incomparability. Recently, however, John Broome has advocated an alternative view, on which value incomparability is explained in terms of vagueness or indeterminacy. In this paper I aim to further Broome’s view in two ways. Firstly, I want to supply independent reasons for thinking that the phenomenon of value incomparability is indeed a matter of the indeterminacy inherent in our comparative predicates. Secondly, I attempt to defend Broome’s account by warding off several objections that worry him, due mainly to Erik Carlson and Ruth Chang.